Eksplorasi Kesadaran dan Faktor Budaya Keamanan Terhadap Keamanan Informasi Dinas Komunikasi dan Informatika Kabupaten XYZ - Michael Parlindungan (AI Society & STMIK Indonesia, 2024)
The role of information technology in the government sector is to organize an efficient, accountable, and transparent electronic government system. The human aspect is the weakest and plays the most important role in maintaining information security. The XYZ District and Communication Agency is important in organizing regional government, including information system management and information security. This study measured the level of information security awareness of 86 employees at the XYZ District Kominfo Agency using a questionnaire based on the HAIS-Q method and aspects of information security culture. The results showed that the level of employee security awareness was at the